Determinants of cervical cancer screening intention among reproductive age women in Ethiopia: A systematic review and meta-analysis - Lahole, Begetayinoral Kussia; Woldamlak, Melkamu; Kussia, Wondafrash (PloS one, 2024)
Cervical cancer is a leading cause of cancer-related mortality in Ethiopia, despite being preventable. Screening programs remain underutilized despite multiple initiatives. This systematic review and meta-analysis aimed to assess the pooled prevalence of intention to undergo cervical cancer screening and its associated factors among Ethiopian women, addressing a significant gap in national data. This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases such as PubMed, EMBASE, CINAHL, Web of Science, Cochrane Library, HINARI, Google Scholar, and African Journals online were searched using specific keywords and Medical Subject Headings (MeSH). Studies were assessed using a standardized appraisal format adapted from the Newcastle-Ottawa Scale (NOS). Data extraction and analysis were performed using Microsoft Excel-10 and STATA 17 software, respectively. Heterogeneity was evaluated with the I2 statistic and publication bias was examined using Egger's test. Meta-analysis employed a random-effects model. Out of the 750 articles retrieved, nine were included in this systematic review and meta-analysis. The pooled prevalence of intention to screen for cervical cancer in Ethiopia was 33% (95% CI: 9%-56%). Factors significantly associated with intention to undergo cervical cancer screening included favorable attitude (POR = 2.15, 95% CI: 1.29, 4.26), good knowledge about cervical cancer screening (POR: 3.49; 95% CI: 2.04, 6.93), and direct subjective norm (POR: 1.54; 95% CI: 1.32, 3.54). Based on the findings of this meta-analysis, it was observed that women's intention toward cervical cancer screening was low. Determinants identified included favorable attitude, direct subjective norm, and good knowledge of cervical cancer screening. To enhance women's intention for cervical cancer screening, strategies, and activities should be developed to positively influence perceptions among women and those who influence their decisions. Additionally, efforts to enhance public awareness about cervical cancer and its prevention are crucial.